Utilization Frequency and Applicability of Translation Approaches in English Contemporary Poetry into Filipino - VILLANUEVA, JOEY M.; GAUUAN, RODEL C. (International Journal of Linguistics and Translation Studies, 2025)
This study assesses the frequency of utilization and the level of applicability of translation approaches in contemporary English poetry into Filipino. It has employed a descriptive research design to address the context in terms of elements, content, and meaning. The instrument that language translation experts validated was used to determine the translation approaches’ applicability level, adopted from the Newmark Translation Checklist. The Communicative Translation was found to be the most frequently utilized based on the principle of “Kung ano ang bigkas ay siyang baybay” (The spelling is the same as how the word is pronounced), along with eight other approaches. It has also been found that the content adequacy referring to the uniform style across various poetic features, the meaning accuracy relevant to the closeness of meaning of the original text to the outcomes, and the overall reflective impact through the practical application of translation practices and techniques towards a wider context of communication have contributed to a significantly high applicability level. However, the sustainability of natural sounds to realize creative arrangement, and the necessity of providing a reliable idiomatic equivalence to sustain the tone, rhythm, and symbolic meaning have significantly influenced moderate applicability level to attain poetic quality, while the textual inadequacy and functional unsuitability, and the absence of an extensive professional translation standard have slightly influenced the content adequacy and overall reflective impact respectively. The results suggest the need for an in-depth study of the principles, approaches, and other relevant topics to achieve quality and excellence in translation.